2015
DOI: 10.1177/0003319715578066
|View full text |Cite
|
Sign up to set email alerts
|

Transradial Coronary Intervention Versus Coronary Artery Bypass Grafting for Unprotected Left Main and/or Multivessel Disease in Patients With Acute Coronary Syndrome

Abstract: The overall safety and efficacy of transradial coronary intervention (TRI) versus coronary artery bypass grafting (CABG) for patients with unprotected left main (UPLM) disease and/or multivessel coronary disease (MVD) presenting with acute coronary syndrome (ACS) have not been established. Consecutive patients with ACS undergoing TRI with drug-eluting stent (n ¼ 1431) or CABG (n ¼ 651) for UPLM and/or MVD were included. A propensity-score matching was performed to adjust for differences in baseline characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Of 173 potentially relevant articles screened initially, we identified 5 RCTs and 17 observational studies with propensity‐score analysis of DES‐PCI versus CABG for LMCAD with ≥6‐month follow‐up enrolling a total of 12,387 patients (Tables and ). These included the NOBLE study , the EXCEL trial , the PRECOMBAT [Bypass Surgery Versus Angioplasty Using Sirolimus‐ Eluting Stent in Patients With Left Main Coronary Artery Disease] study , the SYNTAX [Synergy Between PCI With Taxus and Cardiac Surgery] trial , the DELTA [Drug‐Eluting Stent for Left Main Coronary Artery Disease] registry , the CUSTOMIZE [Appraise a CUSTOMIZEd strategy for left main revascularization] registry , the ASAN‐MAIN [ASAN medical center–left MAIN revascularization] registry , the MAIN‐COMPARE [Revascularization for Unprotected Left Main Coronary Artery Stenosis: Comparison of Percutaneous Coronary Angioplasty Versus Surgical Revascularization] registry , etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 173 potentially relevant articles screened initially, we identified 5 RCTs and 17 observational studies with propensity‐score analysis of DES‐PCI versus CABG for LMCAD with ≥6‐month follow‐up enrolling a total of 12,387 patients (Tables and ). These included the NOBLE study , the EXCEL trial , the PRECOMBAT [Bypass Surgery Versus Angioplasty Using Sirolimus‐ Eluting Stent in Patients With Left Main Coronary Artery Disease] study , the SYNTAX [Synergy Between PCI With Taxus and Cardiac Surgery] trial , the DELTA [Drug‐Eluting Stent for Left Main Coronary Artery Disease] registry , the CUSTOMIZE [Appraise a CUSTOMIZEd strategy for left main revascularization] registry , the ASAN‐MAIN [ASAN medical center–left MAIN revascularization] registry , the MAIN‐COMPARE [Revascularization for Unprotected Left Main Coronary Artery Stenosis: Comparison of Percutaneous Coronary Angioplasty Versus Surgical Revascularization] registry , etc.…”
Section: Resultsmentioning
confidence: 99%
“…Drug‐eluting stents (DES) are suggested to be associated with favorable outcomes for mortality, myocardial infarction (MI), target‐vessel/lesion (TV/TL) repeat revascularization (RRV) (TV‐/TL‐RRV), and major adverse cardiac events as compared with bare‐metal stents (BMS) in PCI for LMCAD . Furthermore, a number of medium‐ to large‐size randomized controlled trials (RCTs) (the NOBLE [Nordic‐Baltic‐British left main revascularization] study and the EXCEL [Evaluation of XIENCE versus Coronary Artery Bypass Surgery for Effectiveness of Left Main Revascularization] trial ) and observational studies with propensity‐score analysis of PCI with DES (DES‐PCI) versus CABG for LMCAD have recently reported mid‐ to long‐term results. Propensity‐score analysis including matching, stratification, and covariate adjustment is a powerful tool to strengthen causal inferences drawn from observational studies .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that, although patients with AMI and thrombosis in unprotected LMCA are at high-risk for substantial mortality, PCI is still associated with a remarkably high short-term and long-term survival rates [11][12][13]. Moreover, in another study reported by Gao et al [14], transradial PCI on unprotected LMCA and/or multivessel disease for patients with ACS had comparable clinical outcomes to CABG, with an advantage of reducing stroke. Contrarily, Baek et al [15] found patients with ST elevation myocardial infarction (STEMI) and LMCA PCI had poor clinical outcome, which is attributable to periprocedural hemodynamic deterioration.…”
Section: Introductionmentioning
confidence: 99%